2020
DOI: 10.1080/13814788.2020.1826431
|View full text |Cite
|
Sign up to set email alerts
|

SERIES: eHealth in primary care. Part 4: Addressing the challenges of implementation

Abstract: Background The implementation of eHealth applications in primary care remains challenging. Enhancing knowledge and awareness of implementation determinants is critical to build evidence-based implementation strategies and optimise uptake and sustainability. Objectives We consider how evidence-based implementation strategies can be built to support eHealth implementation. Discussion What implementation strategies to consider depends on (potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 24 publications
(33 reference statements)
1
25
0
Order By: Relevance
“…A few barriers should be addressed to allow home-based diagnostic testing in practice. An important barrier to eHealth adoption in primary care is, for example, the cost [ 71 ]. In the Netherlands, diagnostic tests ordered by a primary care physician are covered by health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…A few barriers should be addressed to allow home-based diagnostic testing in practice. An important barrier to eHealth adoption in primary care is, for example, the cost [ 71 ]. In the Netherlands, diagnostic tests ordered by a primary care physician are covered by health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Applications like SkinVision could radically change the diagnostic process, require GPs to have a basic understanding of AI and therefore have a greater impact on daily GP practice. Clearly, the degree of disruption to a GP practice will form a barrier to using an eHealth application [ 9 ]. The greater the disruption, the greater the need for reliable testing of technical accuracy and clinical effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…24/7 telemonitoring of patients with diabetes rather than seeing them on a quarterly basis. The lessons learned from the first four papers in the eHealth series are relevant and important to all applications, especially in the case of more complex applications [1,[7][8][9]. Furthermore, patient factors are related to the complexity of applications and need to be considered.…”
Section: Aspects Concerning the Complexity Of Ehealth Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study implementing a precursor of the PHC in the Netherlands, a much higher response rate (70%) in underserved populations was achieved by a culturally adapted postal approach initiated by respondents’ GPs with a follow-up call to non-responders (Groenenberg et al, 2015 ). Research showed that, in general for optimal use of e-Health, different stakeholders such as patients, entrepreneurs, health care professionals and health care insurers should collaborate (Swinkels et al, 2018 ; Van der Kleij et al, 2018 ; Versluis et al, 2020 ). They should preferably be identified and involved at an early stage in the development and implementation of e-Health interventions (Nilsen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%